Risk Factors for Autism in Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The prevalence and risk factors for autism spectrum disorders (ASD) in a cohort of 103 patients with tuberous sclerosis complex (TSC) were determined in a study at the Massachusetts General Hospital, Boston, MA.